1978
DOI: 10.1007/bf01318947
|View full text |Cite
|
Sign up to set email alerts
|

Assessing technical performance at diverse ambulatory care sites

Abstract: The purpose of the large study reported here was to develop and test methods for assessing the quality of health care that would be broadly applicable to diverse ambulatory care organizations for periodic comparative review. Methodological features included the use of an age-sex stratified random sampling scheme, dependence on medical records as the source of data, a fixed study period year, use of Kessner's tracer methodology (including not only acute and chronic diseases but also screening and immunization r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The laboratories' roles continue to change from doing to managing tasks, from producing to monitoring test results, and from receiving requests for testing to providing clinicians with information regarding appropriate testing. POC will continue to emerge as an increasing part of this role, resulting in a need for ongoing education 17,18 , new technologies 1,8 , and review of new groups of at-risk individuals with their own demographic characteristics 19 .…”
Section: Emerging Issuesmentioning
confidence: 99%
“…The laboratories' roles continue to change from doing to managing tasks, from producing to monitoring test results, and from receiving requests for testing to providing clinicians with information regarding appropriate testing. POC will continue to emerge as an increasing part of this role, resulting in a need for ongoing education 17,18 , new technologies 1,8 , and review of new groups of at-risk individuals with their own demographic characteristics 19 .…”
Section: Emerging Issuesmentioning
confidence: 99%
“…2 Proof of this recognition is the work of Osterweis et al, who developed and tested methods for assessing the quality of health care that would be broadly applicable to diverse ambulatory care organizations for periodic comparative reviews. 3 In their work they used Kessner's tracer methodology (including not only acute and chronic diseases but also screening and immunization rates as indicators), and a fixed tracer matrix at all test sites. They found that the actual process of care at all three sites for the three acute conditions (streptococcal pharyngitis, urinary tract infection, and iron deficiency anemia) often differed from the expected process in terms of both diagnostic procedures and treatment outcomes.…”
mentioning
confidence: 99%